TEACHING ENGLISH PRONOUNCATION WITH MEDHODS AND CHALLENGES IN SECONDARY SCHOOLS - Kurbanova Feruza,; Ahrorova Gulsanam Husan qizi, (Ustozlar uchun, 2025)
This article explores the effective teaching of English pronunciation in secondary schools, highlighting both instructional methods and the common challenges faced by educators and learners. It examines various pedagogical approaches, including the communicative approach, audio-lingual method, and the use of phonetic training tools, to enhance learners’ pronunciation accuracy and fluency. The study also investigates prevalent obstacles such as students' native language interference, lack of phonetic awareness, limited classroom time, and insufficient teacher training. Through a review of current practices and empirical studies, the article offers recommendations for integrating pronunciation teaching into the English language curriculum more effectively, ultimately aiming to improve learners' overall oral communication skills.